DEVELOPMENT OF TEACHING METHODS IN PRIMARY CLASS STUDENTS - Qodirova Xolidaxon Ulugbek kizi; Muhammadrafiqova Gulbahor Abrorjan kizi (Лучшие интеллектуальные исследования, 2024)
Annotation: This article will give you some tips on how to engage students in elementary school and how to work with new students. It also provides a variety of methods needed by teachers.